2019
DOI: 10.1038/s41419-019-1842-4
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription-3 drives the high-fat diet-associated prostate cancer growth

Abstract: Prostate cancer (PCa) is the second leading cause of cancer death in men. PCa progression can be associated with obesity. Signal transducer and activator of transcription-3 (STAT3) plays a crucial role in PCa growth. However, whether STAT3 plays a role in high-fat diet (HFD)-associated PCa growth is unknown. Our data show that HFD feeding increases tumor size, STAT3 phosphorylation, and palmitic acid (PA) level in the xenograft tissues of the PCa-bearing xenograft mouse model. In vitro studies show that PA inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Some fatty acids have demonstrated contradictory pre-clinical findings in some in vitro models. For example, palmitic acid (C16:0), an even-chain saturated fatty acid, has been reported to enhance the metastatic potential of melanoma, breast cancer [ 61 ], and prostate cancer cells [ 62 ] in vitro. Furthermore, palmitic acid has been reported to promote colorectal tumorigenesis in vivo [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some fatty acids have demonstrated contradictory pre-clinical findings in some in vitro models. For example, palmitic acid (C16:0), an even-chain saturated fatty acid, has been reported to enhance the metastatic potential of melanoma, breast cancer [ 61 ], and prostate cancer cells [ 62 ] in vitro. Furthermore, palmitic acid has been reported to promote colorectal tumorigenesis in vivo [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the relationship between fat-induced inflammation and PCa [29][30][31][32][33]. In a study using prostate-specific phosphatase and tensin homolog (Pten) −/− mice, we found that an HFD doubled the tumor weight in the model mice but did not increase tumor weight in mice administrated celecoxib, a cyclooxygenase-2 (COX-2) inhibitor, or an anti-interleukin (IL)-6 antibody [29].…”
Section: Fatmentioning
confidence: 95%
“…Further investigation showed that the mechanism involved local inflammation in the prostate gland induced by the HFD, which led to increased counts of tumor-infiltrating myeloid-derived suppressor cells and production of IL-6 by macrophages, thereby inducing PCa growth by suppression of tumor immunity and via the IL-6/signal transducer and activator of the transcription 3 (STAT3) signaling pathway [29]. A previous study showed that the STAT3 pathway plays an important role in HFD-induced PCa progression in an animal model [30], whereas another study investigating prostate tissue from obese PCa-model mice revealed elevated levels of C-X-C motif chemokine ligand (CXCL)12, C-X-C motif chemokine receptor (CXCR)4, and CXCR7 and showed that a CXCR4 agonist inhibited the migration and invasion of PCa cell lines treated with CXCL12 [31]. Additionally, in vivo and in vitro studies suggest that elevated monocyte chemoattractant protein 1 [also known as chemokine ligand (CCL2)] levels produced by adipocytes and elevated levels of the CCL2 receptor chemokine receptor 2 in prostate tissue are involved in HFD-induced PCa progression [32,33].…”
Section: Fatmentioning
confidence: 99%
“…Emerging evidence showing palmitic acid serves not only a fatty acid to produce energy, but also an intracellular signaling molecule involved in the development of cancers 9 . Unlike other fatty acids, palmitic acid boosts the metastatic potential of melanoma and breast cancer cells in a CD36-dependent manner 10 ; and also promotes the growth of prostate cancer by activating the signal transducer and activator of transcription 3 11 . However, the specific role of palmitic acid in promoting CRC growth is not known.…”
Section: Introductionmentioning
confidence: 99%